2020
DOI: 10.1186/s12913-020-05812-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ experience of providing care: a rapid review

Abstract: Background Health care services internationally are refocussing care delivery towards patient centred, integrated care that utilises effective, efficient and innovative models of care to optimise patient outcomes and system sustainability. Whilst significant efforts have been made to examine and enhance patient experience, to date little has progressed in relation to provider experience. This review aims to explore this knowledge gap by capturing evidence of clinician experience, and how this e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…[17][18][19][20] Existing instruments have largely explored individual psychological states and traits, well-being and/ or workplace conditions. 3 Similar constructs are regularly explored in workplace surveys among healthcare staff in Australia and internationally. [21][22][23] While value-based care outcomes include clinician's experiences of providing care, the concept of clinician experience in this context has been ill-defined contributing to challenges in measuring and reporting this outcome from VBHC initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[17][18][19][20] Existing instruments have largely explored individual psychological states and traits, well-being and/ or workplace conditions. 3 Similar constructs are regularly explored in workplace surveys among healthcare staff in Australia and internationally. [21][22][23] While value-based care outcomes include clinician's experiences of providing care, the concept of clinician experience in this context has been ill-defined contributing to challenges in measuring and reporting this outcome from VBHC initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…2 As key actors in health systems and services, clinician's (from all professions) experiences are identified as a key outcome for VBHC initiatives, yet measurement of clinician's experiences of providing care has received limited attention to date. 3 In 2020, a rapid systematic literature review confirmed that the concept of 'clinician experience of providing care' relevant to VBHC was poorly defined with an absence of dedicated measurement tools. 3 The included articles demonstrate that clinician's experiences of providing care are dynamic, influenced by the work context, professional group and patient cohort.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adopting of new technology in healthcare services can be perceived as both an event and a process. According to Iqbal [ 28 ], experience is defined as the knowledge and understanding gained after an event or the process of living through or undergoing an event. This review synthesizes existing empirical knowledge regarding the experiences of occupying the champion role, and the perspectives of health personnel interacting with champions in technology implementation processes.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%